(untitled) (Research, Society and Development, 2022)
This study aims to contribute to the identification and synthesis of evidence from randomized controlled trials on the effects of the use of medicinal plants for the control of depressive symptoms in adults. This is an integrative review, with a search carried out in databases, using the following terms: (medicinal plants OR herbal plants), (depressive disorder OR depression), and (adults OR adult population). Randomized controlled trials; published in original articles available in full; in English or Portuguese, and performed with adults aged 18 to 59 years were included. Duplicate articles that did not meet the inclusion criteria were excluded. The search resulted in a total of 354 studies, with 9 studies included for analysis. Crocus sativus (saffron) was the most used medicinal plant, administered through capsules in a period between 4 and 12 weeks. The use of medicinal plants has shown positive effects in reducing the intensity of depression symptoms, improving memory and mood performance, and improving sleep quality. However, this result should be interpreted with moderation, due to the number of studies and methodological quality.